Self‐Assembled Fluorescent and Antibacterial GHK‐Cu Nanoparticles for Wound Healing Applications. (27th February 2019) - Sun, Leming; Li, Aipeng; Hu, Yanzi; Li, Yang; Shang, Li; Zhang, Lianbing
Abstract: GHK‐Cu is demonstrated with the abilities to improve wound healing, accelerate anti‐inflammatory activity, and repair DNA damage. However, the instability of the GHK‐Cu in biological fluids is always a big challenge for its long‐term and efficient function at the target site. Therefore, the self‐assembled GHK‐Cu nanoparticles (GHK‐Cu NPs) are investigated in this work to solve the instability issue. The crystalline nanostructure within the GHK‐Cu nanoparticles offers them visible and near‐infrared fluorescent properties. With the excellent self‐assembly performance, the antibacterial properties of GHK‐Cu NPs are demonstrated using E. coli and S. aureus . The L929 dermal fibroblast cells are utilized to prove the good biocompatibility and enhanced wound healing applications of GHK‐Cu NPs. This study could pave the way for the design and elaboration of a new class of fluorescent peptides with various biological functions in biomedical applications. Abstract : Self‐assembled fluorescent and antibacterial GHK‐Cu nanoparticles not only overcome the instability of GHK‐Cu monomers in biological fluids for their delivery and performance but also give them new features with great potential in biomedical fields. This study demonstrates that the self‐assembled GHK‐Cu nanoparticles have fluorescent, antibacterial, biocompatible properties, and enhanced wound healing potentials.